Melatonin restores Muc2 depletion induced by V. vulnificus VvpM via melatonin receptor 2 coupling with Gαq - Young-Min Lee; Jong Pil Park; Young Hyun Jung; Hyun Jik Lee; Jun Sung Kim; Gee Euhn Choi; Ho Jae Han; Sei-Jung Lee (Journal of Biomedical Science, 2020)
Abstract Background Melatonin (5-methoxy-N-acetyltryptamine), a hormone produced in the pineal gland, has a variety of biological functions as an antioxidant, but a functional role of melatonin in the regulation of intestinal mucin (Muc) production during bacterial infection has yet to be described in detail. In this study, we investigate the effects of melatonin during Muc2 repression elicited by the Gram-negative bacterium V. vulnificus. Methods Mucus-secreting human HT29-MTX cells were used to study the functional role of melatonin during Muc2 depletion induced by the recombinant protein (r) VvpM produced by V. vulnificus. The regulatory effects of melatonin coupling with melatonin receptor 2 (MT2) on the production of reactive oxygen species (ROS), the activation of PKCδ and ERK, and the hypermethylation of the Muc2 promoter as induced by rVvpM were examined. Experimental mouse models of V. vulnificus infection were used to study the role of melatonin and how it neutralizes the bacterial toxin activity related to Muc2 repression. Results Recombinant protein (r) VvpM significantly reduced the level of Muc2 in HT29-MTX cells. The repression of Muc2 induced by rVvpM was significantly restored upon a treatment with melatonin (1 μM), which had been inhibited by the knockdown of MT2 coupling with Gαq and the NADPH oxidase subunit p47 phox. Melatonin inhibited the ROS-mediated phosphorylation of PKCδ and ERK responsible for region-specific hypermethylation in the Muc2 promoter in rVvpM-treated HT29-MTX cells. In the mouse models of V. vulnificus infection, treatment with melatonin maintained the level of Muc2 expression in the intestine. In addition, the mutation of the VvpM gene from V. vulnificus exhibited an effect similar to that of melatonin. Conclusions These results demonstrate that melatonin acting on MT2 inhibits the hypermethylation of the Muc2 promoter to restore the level of Muc2 production in intestinal epithelial cells infected with V. vulnificus.